1997
DOI: 10.1094/phyto.1997.87.9.915
|View full text |Cite
|
Sign up to set email alerts
|

Fusarium oxysporum f. sp. cubense Consists of a Small Number of Divergent and Globally Distributed Clonal Lineages

Abstract: A worldwide collection of Fusarium oxysporum f. sp. cubense was analyzed using anonymous, single-copy, restriction fragment length polymorphism (RFLP) loci. Several lines of evidence indicated that this pathogen has a clonal population structure. Of the 165 isolates examined, only 72 RFLP haplotypes were identified, and nearly half the isolates were represented by the five most common haplotypes. Individuals with identical haplotypes were geographically dispersed, and clone-corrected tests of gametic disequili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
114
1
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(131 citation statements)
references
References 25 publications
15
114
1
1
Order By: Relevance
“…The results of our study are similar in lines with those obtained by Kistler (1997) and Gherbawy (1999) who suggested that certain F. oxysporium isolates within a formae speciales may be genetically less similar to each other than those isolated as nonpathogenic strains or those isolated as a group in the other formae speciales (Vilgalys and Cubeta, 1994;Banniza et al, 1996;Kistler, 1997;Koening et al, 1997;O'Donnell et al, 1998;Neeraja et al, 2002 ;Runhua et al, 2002).…”
Section: C2-2supporting
confidence: 91%
“…The results of our study are similar in lines with those obtained by Kistler (1997) and Gherbawy (1999) who suggested that certain F. oxysporium isolates within a formae speciales may be genetically less similar to each other than those isolated as nonpathogenic strains or those isolated as a group in the other formae speciales (Vilgalys and Cubeta, 1994;Banniza et al, 1996;Kistler, 1997;Koening et al, 1997;O'Donnell et al, 1998;Neeraja et al, 2002 ;Runhua et al, 2002).…”
Section: C2-2supporting
confidence: 91%
“…This clonal lineage consisted of only seven highly similar AFLP genotypes, and all of its members shared identical or nearly identical EF-1␣ and IGS rDNA sequences and possessed only MAT1-1 idiomorphs, indicating that they were of clonal origin. To date, molecular epidemiological studies that have identified fungal pathogens with a highly clonal population structure are restricted to a relatively small number of clinically (8,9), zoologically (17), and agriculturally (4, 5, 11) important species, including members of the FOC (13,29). However, most clinically important fungi investigated to date isolates indicated by shading.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, various DNA-based tools have been used to separate F. oxysporum f. sp. cubense into a number of clonal lineages that more or less correspond to their grouping based on VCGs (6,22,38,59).…”
mentioning
confidence: 99%